Product Listing Agreements (PLAs): A New Tool for Reaching Quebec's Pharmaceutical Policy Objectives? - Mélanie Bourassa Forcier and François Noël (Law & Governance, 2013)
[This article was originally published in Healthcare Policy 9(1).] Product listing agreements (PLAs) with pharmaceutical manufacturers are increasingly viewed as an innovative and useful tool in the effort to control drug expenditures. To date, Quebec is the only province that has been reluctant to enter into such agreements, arguing that their confidential nature may lead to a disparity in coverage between individuals covered by the public plan and those covered by private insurance. While PLAs may, in fact, present such a risk, in this paper we will argue that when used correctly, these agreements are actually tools that could help attain all four of the objectives set out in Quebec's policy on medications, namely: (a) improved access to drugs, (b) fair and reasonable drug pricing, (c) optimal drug use and (d) maintaining a dynamic biopharmaceutical industry in Quebec.
Keywords: Product listing agreements (PLAs) with pharmaceutical manufacturers are increasingly viewed as an innovative and useful tool in the effort to control drug expenditures. To date, Quebec is the only province that has been reluctant to enter into such agreements, arguing that their confidential nature may lead to a disparity in coverage between individuals covered by the public plan and those covered by private insurance. While PLAs may, in fact, present such a risk, in this paper we will argue that when used correctly, these agreements are actually tools that could help attain all four of the objectives set out in Quebec's policy on medications, namely: (a) improved access to drugs, (b) fair and reasonable drug pricing, (c) optimal drug use and (d) maintaining a dynamic biopharmaceutical industry in Quebec.